Niche emergence as an autocatalytic process in the evolution of ecosystems. (7th October 2018) - Cazzolla Gatti, Roberto; Fath, Brian; Hordijk, Wim; Kauffman, Stuart; Ulanowicz, Robert
Highlights: Niche partitioning is insufficient or, at least, not entirely convincing as a way to understand niche emergence and the related biodiversity. We propose that niche emergence is what mostly drives ecological diversity. We view ecosystems in terms of autocatalytic closed sets with self-sustaining interaction networks. We provide some examples of such ecological autocatalytic networks. We show how this can give rise to an expanding process of niche emergence (both in time and space) and how these networks have evolved over time (so-called evoRAFs). We suggest that EvoRAFs can be expected to show a power-law in the size distribution of extinction events in ecosystems. We elaborate on our earlier argument that new species create new niches, and that biodiversity is therefore an autocatalytic process. Abstract: The utilisation of the ecospace and the change in diversity through time has been suggested to be due to the effect of niche partitioning, as a global long-term pattern in the fossil record. However, niche partitioning, as a way to coexist, could be a limited means to share the environmental resources and condition during evolutionary time. In fact, a physical limit impedes a high partitioning without a high restriction of the niche's variables. Here, we propose that niche emergence, rather than niche partitioning, is what mostly drives ecological diversity. In particular, we view ecosystems in terms of autocatalytic sets: catalytically closed and self-sustaining reaction (or interaction) networks. We provide some examples of such ecological autocatalytic networks, how this can give rise to an expanding process of niche emergence (both in time and space), and how these networks have evolved over time (so-called evoRAFs). Furthermore, we use the autocatalytic set formalism to show that it can be expected to observe a power-law in the size distribution of extinction events in ecosystems. In short, we elaborate on our earlier argument that new species create new niches, and that biodiversity is therefore an autocatalytic process.